Adoption of Children of Different Religions in the Perspective of the Civil Code Juridical Review and Social Implications in North Sumatra - Fajriawati Fajriawati (SEAN Institute, 2026)
This study examines the practice of adopting children of different religions from the perspective of the Civil Code with a focus on the analysis of the North Sumatra region. Through a sociological and empirical juridical approach, this study identifies the legal dynamics and social implications of the practice of adopting children of different religions in the multicultural society of North Sumatra. By analyzing data on applications for adoption of children of different religions at the District Court in North Sumatra in 2022-2024, this study shows that 73.1% of applications for adoption of children of different religions were granted with the primary consideration of the best interests of the child. The results of the study indicate a tension between the provisions of the Civil Code that do not specifically regulate adoption of different religions with developing social practices and jurisprudence, the identified social implications include challenges to family integration, adjustment of children's identity and adaptation to the community. This study recommends harmonization of adoption law that takes into account the socio-cultural diversity of North Sumatran society while still prioritizing the best interests of the child.